2006
DOI: 10.1016/j.enpol.2004.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Green energy market development in Germany: effective public policy and emerging customer demand

Abstract: This paper reviews the development of renewable energy in Germany from 1973 to 2003. It investigates the relative importance of energy policy and green power marketing in shaping the renewable energy market. More than a decade of consistent policy support for renewables under the feed-in law (StrEG) and its successor (EEG) has been an important driver for increasing renewable electricity generation to date, putting the country in a better position than most of its peers when it comes to achieving European Unio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
202
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 350 publications
(211 citation statements)
references
References 5 publications
5
202
0
4
Order By: Relevance
“…A comparable study by Guidolin et al also found that positive government policies in form of incentives and subsidies positively influenced PV N. Opiyo diffusions across 11 countries [9]. Wustenhagen found that positive government policies, especially feed-in-tariffs (FiT), were largely responsible for the boom in PV installation in Germany [10]. Zhang et al found that in addition to positive regional governments' policies, costs also played significant roles in PV diffusions across Japan [11].…”
Section: Impacts Of Subsidies On Pv Diffusionsmentioning
confidence: 84%
“…A comparable study by Guidolin et al also found that positive government policies in form of incentives and subsidies positively influenced PV N. Opiyo diffusions across 11 countries [9]. Wustenhagen found that positive government policies, especially feed-in-tariffs (FiT), were largely responsible for the boom in PV installation in Germany [10]. Zhang et al found that in addition to positive regional governments' policies, costs also played significant roles in PV diffusions across Japan [11].…”
Section: Impacts Of Subsidies On Pv Diffusionsmentioning
confidence: 84%
“…Studies in most European countries such as Sweden [75,76], Norway [77][78][79], the Netherlands, and Germany [80,81] indicate that the development of alternative food networks such as the farmers' markets is often based on "modern" and more "commercial" quality definitions, stressing environmental sustainability or animal welfare, and on innovative (and retailer-led) forms of marketing [82]. According to Evans et al [83], the general move towards "ecological modernization" may reconcile agriculture and environment in ways which continue to support agricultural production.…”
Section: Farmers' Marketsmentioning
confidence: 99%
“…In Brazil, for example, Eucalyptus is crucial for pulp and paper production [4]. In Europe and particularly Germany, a change in energy policies towards reduction in use of fossil fuels and towards a stronger use of renewable energy, as outlined in the "Erneuerbare Energien Gesetz" (EEG 2004) [5], marked an increase in fast-growing tree production. Short rotation coppice can have a rotation cycle of 2-3 (short), 4-10 (medium), or 10-20 years (long), depending on management objectives [6,7].…”
Section: Introductionmentioning
confidence: 99%